2014
DOI: 10.5324/nje.v24i1-2.1807
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviors and family characteristics in early childhood influence caries development. A longitudinal study based on data from MoBa

Abstract: Background: Lifestyle diseases including dental caries are partly preventable, and associated with health behavior. Establishing favorable health behavior is one main challenge both in general and dental health services. The purpose of this paper was to focus on cross-disciplinary research that has the potential to prevent development of both dental caries and other lifestyle diseases. More specifically the aim was to study how family characteristics and health behavior in pregnancy and early childhood influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The highest-level evidence came from the 6 cohort studies, for which analysis classified the risk of bias to be very serious, primarily due to risk of confounding and weaknesses in experimental design. Five of the 6 studies showed significantly higher ECC in children who consumed a higher level of drinks containing free sugars (vs. lower/no drinks; Wendt and Birkhed 1995; Wendt et al 1996; Warren et al 2009; Watanabe et al 2014; Wigen and Wang 2014), and 1 study found no significant difference (Yonezu et al 2006). However, this study compared ECC between those consuming 3 and 2 drinks per week and not nonconsumers.…”
Section: Resultsmentioning
confidence: 98%
“…The highest-level evidence came from the 6 cohort studies, for which analysis classified the risk of bias to be very serious, primarily due to risk of confounding and weaknesses in experimental design. Five of the 6 studies showed significantly higher ECC in children who consumed a higher level of drinks containing free sugars (vs. lower/no drinks; Wendt and Birkhed 1995; Wendt et al 1996; Warren et al 2009; Watanabe et al 2014; Wigen and Wang 2014), and 1 study found no significant difference (Yonezu et al 2006). However, this study compared ECC between those consuming 3 and 2 drinks per week and not nonconsumers.…”
Section: Resultsmentioning
confidence: 98%
“…Toothbrushes must be changed every 3 months. [9] The study results revealed that there is a statistically signi cant difference in the frequency of dentist visits between urban children and rural participants (p = 0.026). Participants from rural areas (48%) reported never having visited a dentist compared to 40% from urban areas.…”
Section: Discussionmentioning
confidence: 86%
“…This means giving more attention to preventive care, like teaching kids and their parents about how important oral health is, promoting oral health in schools, and doing preventive things like putting sealants in fissures and repairing molar deciduous teeth to keep them from getting cavities. [1,2,16] Also, most of the people who came to our clinic for treatment came from low-income or low-social-status homes, and their parents needed more education about things like what to eat and how to brush their teeth.…”
Section: Discussionmentioning
confidence: 99%
“…The impact could disrupt the child's education by causing a variety of issues, including difficulty ingesting and rapid onset of illness. [1,2] Deciduous teeth play a crucial role in the stimulation and formation of dental arches, normal occlusion connections, maintenance of beauty, development of speech function, improvement of mastication efficiency, and enhancement of quality of life. There have been numerous initiatives to preserve the teeth's functionality.…”
Section: Introductionmentioning
confidence: 99%